Isis on the Nile : Egyptian gods in Hellenistic and Roman Egypt : proceedings of the IVth International Conference of Isis Studies, Liège, November 27-29, 2008 : Michel Malaise in honorem - Bricault, Laurent.; Versluys, M. J.; Malaise, Michel. (Religions in the Graeco-Roman World, 2010)
The diffusion of the cults of Isis is recently again intensively studied. Research on this fascinating phenomenon has traditionally been characterised by its focus on L'Égypte hors d'Égypte, while developments in Hellenistic and Roman Egypt itself were often seen as belonging to a different domain. This volume tries to overcome that unhealthy dichotomy by studying the cults of Isis in Hellenistic and Roman Egypt itself in relation to developments in the Mediterranean at large. The book not only presents an overview of the most important deities, often based on new or unpublished material, but also pays ample attention to the cultural processes behind Isis on Nile, like relations between style and identity, religious choice, social- and cultural memory and Egypt's view of its own past.